IMPLEMENTATION OF THE FAMILY HOPE PROGRAM DURING THE COVID-19 PANDEMIC IN SELATPANJANG TIMUR VILLAGE - Julieta Putri Pratila Utami; Dedi Kusuma Habibie (ADISAM Publisher, 2023)
Well-being is destination main from every country including Indonesian state. Poverty is a global problem that is experienced by every country in the world . To eradicate poverty, one of them issued a policy for the poor which was realized in the form of the Family Hope Program (PKH). Family Program Hope is a program that provides help cash or non-cash to family poor (KM), this program covers enhancement quality source power human (HR), namely education, health and well-being social. Study this aim for knowing how family program implementation hope in the village Selatpanjang East. Study this use study descriptive qualitative and in focus study use George Edward III's theory, namely Communication (Communication), Resources (Resources), Attitude (Dispotition/Attitude), Structure Bureaucratic (Bureaucratic Structure). Location selected research _ in study this namely in the Village Selatpanjang East Regency Island Meranti. Method study this use method qualitative with technique data collection based on observation, interview, and documentation. Results study this show that implementation from family program hope in the village Selatpanjang East not yet implemented with good. Factors that become blocker in implementation of this program is from indicator communication, resources power and structure bureaucracy.